1998
DOI: 10.1002/ana.410430310
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis in myophosphorylase deficiency (McArdle's disease)

Abstract: Inherited deficiency of myophosphorylase leads to glycogen storage disease type V (McArdle's disease). We performed mutation analysis in 9 patients of eight unrelated families from Germany with typical clinical presentation of myophosphorylase deficiency. Beside previously described mutations we identified four novel mutations in the myophosphorylase gene. Four patients were homozygous for a nonsense mutation Arg49Stop that has been reported to be the most common mutation in white patients. Two affected siblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…The mutation c.1768 +1G>A has been reported in patients from different ethnic background (Martin et al 2001b, Tsujino et al 1994b. In this regard, the mutations p.R94W and p.R576X identified in two patients, were previously described in McArdle disease patients of German origin (Deschauer et al 2003, Vorgerd et al 1998 suggesting that these mutations are not private, and might be found in individuals from other ethnic backgrounds. The p.K754NfsX49, p.A660D, p.R602W, p.A704V, c.1827G>A and p.L5VfsX22 mutations have already been reported in Spanish patients with McArdle disease (Fernandez-Cadenas et al 2003, Martin et al 2001a, Martin et al 2001b, Rubio et al 2006.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The mutation c.1768 +1G>A has been reported in patients from different ethnic background (Martin et al 2001b, Tsujino et al 1994b. In this regard, the mutations p.R94W and p.R576X identified in two patients, were previously described in McArdle disease patients of German origin (Deschauer et al 2003, Vorgerd et al 1998 suggesting that these mutations are not private, and might be found in individuals from other ethnic backgrounds. The p.K754NfsX49, p.A660D, p.R602W, p.A704V, c.1827G>A and p.L5VfsX22 mutations have already been reported in Spanish patients with McArdle disease (Fernandez-Cadenas et al 2003, Martin et al 2001a, Martin et al 2001b, Rubio et al 2006.…”
Section: Discussionmentioning
confidence: 71%
“…Eighteen additional mutations were identified. Of them, nine were reported elsewhere: c.13_14del, p.L5VfsX22; (Rubio et al 2006, in press); c.280C>T, p.R94W (Deschauer et al 2001); c.1726C>T, p.R576X (Vorgerd et al 1998); c.1768 +1G>A (Tsujino et al 1994b); c.1804C>T, p.R602W (Martin et al 2001a); c.1827G>A (Fernandez-Cadenas et al 2003); c.1979C>A, p.A660D ); c.2111C>T, p.A704V (Martin et al 2001a); and c.2262del, p.K754NfsX49 , Martin et al 2001b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A GUG start codon identified in the CYP2C19 gene in a poor metabolizer patient was not translated in an in vitro mutagenesis test [Ferguson et al, 1998]. Similarly, in a clinical case of McArdle's disease with a GTG start codon in the myophosphorilase gene, the enzyme could not be detected by muscular staining, suggesting a loss of expression [Vorgerd et al, 1998]. These examples are congruent with the most accepted model of eukaryotic translation initiation where the canonical start site is only the first AUG [Kozak, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…The PYGM gene (20 exons) was amplified from genomic DNA (patients 2 -4) in 14 segments with intronic primers, and sequences of exons and flanking intron regions were compared with the revised genomic sequence of PYGM. 34,35 The 13 exons and their flanking intron sequences of the PRKAG3 gene (NT_005289) were amplified in eight intervals from genomic DNA of patients 2 -6.…”
Section: Patientsmentioning
confidence: 99%